Depression, anxiety, and stress among indonesian migrant workers in hong kong: prevalence, demographic differences, and psychosocial correlates - Khairul Bariyyah; Adi Atmoko; Evania Yafie; Muhammad Alfan; Diani Akmalia Apsari; Siti Nurhaliza; Rosita Purnama Sari; Innaya Rahmania Dewi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
This study aimed to estimate the prevalence and severity of depression, anxiety, and stress, examine differences across demographic and occupational characteristics, and identify psychosocial correlates associated with these symptoms. A cross-sectional quantitative study was conducted using a convenience sample of 54 Indonesian MDWs in Hong Kong. Participants completed the Depression, Anxiety, and Stress Scale-21 (DASS-21). Given the small sample size, non-parametric analyses, exact effect sizes with 95% confidence intervals, Benjamini–Hochberg false discovery rate (FDR) correction, and multiple regression models with a maximum of four predictors were employed. Mean (SD) scores were 6.22 (8.08) for depression, 8.00 (8.94) for anxiety, and 10.00 (10.13) for stress. Based on DASS-21 severity classifications, 14.8% of participants reported moderate-to-extremely severe depression, 37.0% anxiety, and 16.7% stress, while 40.7% experienced at least one condition at a moderate or higher level. The DASS-21 demonstrated high internal consistency (Cronbach’s α = .88, .87, and .92 for depression, anxiety, and stress, respectively). Poor or fair employer relationships were consistently associated with higher depression, anxiety, and stress scores and remained significant after adjustment for working hours, rest days, and social support (all p < .03). These findings highlight employer–employee relationship quality as a key psychosocial correlate of psychological distress and a potential target for workplace interventions and policy. Larger, representative studies are needed to confirm these findings.